Life Extension of Draw Bar’s Holder on 6K Type Electric Locomotive - HAN Tong-yang; LIU Zhi-ming (机车电传动)
Reasons of draw bar’s holder cracks on 6K type electric locomotive were analyzed, and ANSYS were applied for finite element analysis of the draw bar’s holder. The fatigue strength was evaluated and actual dynamic stress was tested. With considering the different stress and bearing structure characteristics of the draw bar’s holder, the corresponding optimization for life extension was designed to ensure prolonged life of 6K type electric locomotive to 10 years.